The Effect of Giving Ketepeng (Cassia Alata L) Leaves on Allergic Mice (Mus Musculus) Skin Eosinophils - Annisa Nur Rizky; I Gede Andika Sukarya; Nursalinda Kusumawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Allergy is a disease that is a major health problem throughout the world. This research was to determine the effect of administering ketepeng leaf paste on the increase and decrease in eosinophil cells in the skin of allergic mice induced by ovalbumin. This type of research uses pure experiments (True Experiment Research) with research samples consisting of 30 male mice divided into 3 groups, namely the control group, the allergic group, and the allergic group that was given a smear of paste. The allergy group that was given the paste responded to a decrease in eosinophils on day 14 when compared to the allergy group that was not given the ketepeng leaf paste. Statistical tests using the One Way Anova test obtained a p value of 0.000. It was found that there was an effect of giving ketepeng leaf paste on reducing eosinophil cells in the skin tissue of allergic mice given ketepeng leaf paste.